Molecular and biophysical remodeling of the blood–brain barrier in glioblastoma: mechanistic drivers of tumor–neurovascular crosstalk - Abikenari, Matthew; Sjoholm, Matthew Adam; Liu, Justin; Nageeb, George; Ha, Joseph H.; Wu, Janet; Ren, Alexander; Sayadi, Jamasb; Lim, Jaejoon; Cho, Kwang Bog; Verma, Rohit; Medikonda, Ravi; et al. (Frontiers in Physics, 2025)
Glioblastoma (GBM) resists conventional treatment in large part because the blood–brain barrier (BBB) and its tumor-modified counterpart, the blood–tumor barrier (BTB), form a spatially heterogeneous, actively regulated interface that governs transport. In this setting, permeability, perfusion, and efflux are decoupled so radiographic contrast enhancement is an imperfect surrogate for true therapeutic exposure. Based on breakthroughs in vascular biology, imaging, and transport modeling, single-cell and spatial profiling, and translational delivery studies, we demonstrate how vascular co-option, hypoxia-induced remodeling, and barrier dysregulation generate gradients from relatively intact margins to leaky but sparsely perfused cores. In addition to their function in regulating molecular traffic, perivascular cells and astrocyte programs affect local immune niches that enable myeloid suppression and exclusion of T-cells and suppress systemic immunotherapies. New tools, from novel MRI/PET methods to intravital microscopy and microphysiologic “BBB-on-chip” platforms, facilitate quantitative measurement of regional transport and drug levels. These observations indicate three interrelated paths to enhanced therapy: temporarily normalizing or reversibly opening the barrier, avoiding it by targeted regional delivery, and rationally designing drugs that account for transport and efflux limitations. The integration of barrier modulation with immunotherapies in preclinical models enhances intratumoral exposure and efficacy. Lessons from other neurologic illnesses highlight both the dangers of uncontrolled opening and the potential of localized, reversible modulation. We support a “BBB-first” paradigm that treats the barrier as a quantifiable, targetable organ and demands trials stratified by barrier phenotype and correlating clinical outcome with regional exposure and immune access.